2009
DOI: 10.1002/ceat.200900201
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Heat Integration in a Periodically Operated Cascade of Catalytic Fixed‐Bed Reactors

Abstract: Forced periodic operation can lead to improved reaction processes. Such operation is studied for the example of the application of a cascade of connected adiabatic fixed-bed reactors to perform catalytic total oxidation. It is shown that the periodic operation of the configuration considered allows an autothermal operation. The concept can outperform classical reverse-flow operation concerning the reduction of slips of unconverted feed. A simple model based on the assumption of a hypothetical countercurrent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The domain around V sw /V th =1 is the domain with the highest potential for heat recuperation as was shown in numerous studies (e.g. [1,37,45]). extinguished (E).…”
Section: Multi-species Systemmentioning
confidence: 54%
See 1 more Smart Citation
“…The domain around V sw /V th =1 is the domain with the highest potential for heat recuperation as was shown in numerous studies (e.g. [1,37,45]). extinguished (E).…”
Section: Multi-species Systemmentioning
confidence: 54%
“…The singularities expected in a loop reactor were characterized [45,46] by plotting the domain of frozen rotating patterns in the plane of the inlet temperature vs the switching velocity (V sw /V th , denoted as Flow rate ratio γ in Fig. 5).…”
Section: Slow Switchingmentioning
confidence: 99%
“…When RFR works, complex and characteristic phenomena are experimentally-observed, see [14,15,16] and references therein. They are also observed in numerical simulations with the aid of mathematical models, see [7,10,11,14,15,16,17] and references therein. According to numerical simulations by Budhi et al, complicated and sensitive asymptotic behavior of solutions can be observed, see [2].…”
Section: Introductionmentioning
confidence: 82%
“…each simulation, the switching time has been step-wise increased and the previously computed solution has been employed as initial condition for the following simulation. We note that the number of periods needed for the NTW to achieve regime conditions increases dramatically as the points S i are approached (Zahn et al, 2009). It must be also stressed that, although not reported in Fig.…”
Section: Effect Of the Switch Strategy: Stability And Performancementioning
confidence: 91%
“…In the context of catalytic combustion of volatile organic compounds, Haynes and Caram (1994) compared, for example, the performances of a NTW of two reactors with those of the reverse-flow-reactor, while Brinkmann et al (1999) analyzed the performance of a network of three reactors. Several studies of NTWs of three or more reactors have been also performed focusing on the analysis of complex reactor dynamics Altimari et al, 2006;Zahn et al, 2009). Velardi and Barresi (2002) and Sheinman and Sheintuch (2009) analyzed the performance of a NTW of catalytic reactors where methanol synthesis process takes place.…”
Section: Article In Pressmentioning
confidence: 99%